Izkušnje medicinskih sester z albansko govorečimi pacienti - Božič, Anika (Obzornik zdravstvene nege, 2022)
Introduction: Nurses often face linguistic and cultural challenges when dealing with Albanian-speaking patients. The aim of the study was to investigate nurses' experiences with Albanian-speaking patients, to identify potential challenges and propose solutions.Methods: A qualitative research method was used. A purposeful quota sample of 12 nurses working in primary and secondary levels of healthcare was interviewed in November 2021 using semi-structured questionnaires. The data collected were subjected to text analysis. Results: Four thematic groups that describe the studied phenomena were identified: (1) the first encounter with Albanian-speaking patients, (2) characteristics of dealing with Albanian-speaking patients, (3) ways to overcome language barriers, (4) suggestions to overcome barriers in medical treatment. Discussion and conclusion: The challenges concerning Albanian-speaking patients have been known in Slovenia for a few years, but this problem has not been significantly dealt with. The results show that overcoming language and cultural barriers currently depends on the improvisation of healthcare professionals, which may result in oversights. Further research should include the aspect of Albanian-speaking patients.
Keywords: barriers; communication; competences; culture; healthcare professionals; kompetence; komunikacija; kultura; ovire; zdravstveni delavci